Pengaruh Penghindaran Pajak Terhadap Nilai Perusahaan Dengan Variabel Moderasi Transparansi dalam Perspektif Akuntansi Syariah - Dijan Novia Saka; Rieva Madyna Istighfa (Al-Muhasib: Journal of Islamic Accounting and Finance, 2021)
Tax avoidance and transparency activities influence the value of the company because taxation is a reduction of profits. The smaller the profit obtained, the greater the tax paid. On the one hand, if the level of transparency of the company is high, it can reduce the level of managerial opportunistic behavior. So that the impact of this will benefit the company and its shareholders. This study aims to examine how the impact of tax avoidance and transparency on company value. Where the result is tax avoidance has a significant effect of 0.000 <0.05 and the t-test value of 6.149> 2.048 on the company's value, so the tax avoidance variable has a significant negative effect on firm value. While transparency has a significant effect of 0.001 <0.05 and for the t-test value of 3,649 > 2,048 on Company Value. So that the transparency of its influence is positive on the value of the company, the higher the level of transparency of the company doing tax avoidance, the higher the value/price of the company.